Evaluación con ecografía Doppler en la nefropatía diabética en los pacientes diabéticos tipo 2, del hospital de Especialidades FF. AA. N° 1, en el periodo de octubre a diciembre de 2013. - Tamayo Guamán, Jhon D. (2014)
Diabetic nephropathy (DN) is one of the most serious complications of diabetes mellitus. Doppler ultrasound is an ideal screening method, which is not contraindicated in patients with renal failure. Ultrasound Doppler indices measured in the intra-renal arteries show changes in the values of resistance index (RI ) . Accordingly, the IR is useful for predicting the deterioration of renal function, which can be correlated with the clinical characteristics and biochemical values ND renal dysfunction. We conducted a analytical epidemiological documentary study of cases and controls, prospective, transversal which aims to evaluate the role of Doppler ultrasound renal to determine the values of IR in diabetic patients and compared with healthy control subjects was performed and correlate with the values of albuminuria and serum creatinine of patients presenting to Specialty Hospital FF. AA. N ° 1. This study included 50 patients (mean age 55.7 ± 9.7), which were classified according to albuminuria in normoalbuminuira 18, 23 with micoralbuminuria and 9 macroalbuminuria. The control group included 15 healthy subjects (mean age 46.3 ± 12.1). Were underwent renal Doppler study of intrarenal arteries to assess the IR, which showed that patients with normoalbuminuria has an IR of 0 , 63 ± 0.04 , while microalbuminuria with IR 0.04 ± 0.72 and macroalbuminuria with IR 0.03 ± 0.81 . The control group showed an RI of 0.56 ± 0.05. In conclusion we have to lift IR is accompanied by the progression of diabetic nephropathy, with a good correlation with albuminuria and serum creatinine. IR disturbances begin to observe in patients with microalbuminuria , so should be considered as an early indicator of renal dysfunction . Keywords: Duplex ultrasound, Intrarenal resistivity index, Diabetic nephropathy, Diabetes mellitus, Serum Creatinine, 24-Hour Urine Protein, Albuminuria.